The Self-concept of Adolescent Bully Victim: : Semiotic Analysis on Overcomer (2016) Animated Short by Hannah Spangler - Nadia, Nadia Salsabila (English Language, Linguistics, Literature, And Education Journal, 2023)
Self-concept is the process of an individual’s conceptualization of oneself, which is an individual’s subjective feelings and a complex combination of conscious or unconscious thoughts, attitudes, and perceptions. In adolescence, identity development occurs if at this time an individual fails to pass it and it will cause several problems such as bad self-image, self-development disorders, low self-esteem, identity changes, and even role confusion which leads to a negative self-concept. This research aimed to investigating the portrayed of negative self-concept of adolescent bully victim in one of the short animated films by Hannah Spangler, Overcomer (2016). This research uses qualitative and interpretative method by analyzing the signs, objects, and interpretants related to Charles Sanders Pierce theory, then analyze the self-concept of the main character by used Muchlisin Riadi’s theory (2013). The data of this research is taken from watching, listening, and observing the short animated film Overcomer (2016). The result of this research shows the negative self-concept that the main character has as an adolescent bully victim, namely having an identity as an unsociable or introverted person, the ideal-self considers herself as a person who is not talented or does not deserve any friends. Low self-esteem makes her think that she is an ugly person. Body image sees herself as a failure, useless, and worthless. As a result of having low self-esteem and body image, Hannah assumes that she has no role in social life. Keywords: Animated Short, Charles Sanders Pierce, Self-concept, Semiotic Analysis